Social Orphancy: Sociological Analysis of Personal Motives to Child Abandonment - Uasheva, Aizhan ÐšÐ°yrgeldinovna; Buharova, Anar Bulatovna; Ayazbayeva, Asemgul Temirkhanovna; Isahova, Gulazya Duysenhanovna (International Review of Management and Marketing, 2016)
This paper is devoted to the study of social orphancy reasons and growing number of abandoned children. Authors stress on personal factors affecting abandonment by mothers. Urgency of that issue is caused by the need for comprehensive study of social orphancy via negative social phenomena: poverty, unemployment, social deviation which may potentially adversely affect individual behavior of any unfavorable socialization's victim. Personal factors of child abandonment were studied in two aspects: considering mother's deprivation of abandoners and their socialization in childhood. Problems referred to by abandoning mothers are absence of accommodation, money, work, etc., i.e., objective problems of everyday life, but to a great extent that is the heritage of personal and family nature connected with unfavorable previous generations and forgetting about morals. Keywords: childhood sociology, social orphancy, socialization in childhood, mother's deprivation. JEL Classifications: I380, I180, I150, Z130, Z180